PENDEKATAN PEMBELAJARAN SAINTIFIK UNTUK MENINGKATKAN KREATIVITAS DAN HASIL BELAJAR MATERI KEGIATAN PRODUKSI PADA SISWA KELAS VII D SMPN 1 WINONG - Harnanik, Harnanik (Fakultas Ekonomi, Universitas Negeri Semarang, 2014)
The objectives of this study were to determine whether a scientific approach to learning can improve learning outcomes matter of creativity and production activities in class VII D SMPN1 Winong. This research is a class action (PTK), which consists of 3 cycles, each cycle consisting of four phases, namely planning, action, observation and reflection. The results showed keaktivitas student learning with scientific learning approach in the first cycle of 59% with a sufficient criterion increased 16% with high criteria on the second cycle ddan again increased 6% with high criteria of the third cycle. Thoroughness of learning outcomes in the first cycle at 69% increased 15% in the second cycle and increased again by 10% in the third cycle. Percentage of average score of creative products in the first cycle of 67% with sufficient criteria has increased 8% with high criteria and an increase again 8% with high criteria in the third cycle.Â